Theoretical Underpinnings of the Determinants of Firm Performance: A Literature Review - Parmar, Kanaiyalal Shantilal; Nagi Reddy, V.; Chauhan, Yogesh Kumar (Indian Journal of Finance, 2015)
Literature survey on the determinants of firm performance indicates that earlier studies offered no consensus over the subject to confirm the factors and direction of these factors which determine firm performance. We maintained that the results for firm performance at an aggregate level are not valid for the firms classified based on industries. We also argued that firms cannot increase their performance indefinitely with increase in their sizes. After a certain point, firm performance decreases with the increase in firm size. Furthermore, in view of the recent economic reforms, it is essential to evaluate the role of business groups in India.